Chinese Trader Perceptions on Sourcing and Consumption of Endangered Seafood - Fabinyi, Michael; Barclay, Kate; Eriksson, Hampus (Frontiers in Marine Science, 2017)
Growing trade networks through globalisation have expanded governance of local environments to encompass multiple scales. The governing role of market actors, such as traders and consumers in importing countries, has been recognized and embraced for sustainable seafood sourcing and trade. The perceptions that affect the conduct of these actors are a potential influence on governance of distal environments. In this paper we investigate the perceptions of sea cucumber traders in China. Sea cucumbers are an important global fishery commodity predominantly traded to China, the world’s largest seafood market, and seven traded species are endangered globally. We examine what traders and consumers in China perceive as important issues in seafood markets, and where they perceive the responsibility for sustainable fisheries to lie, to interpret what scope there is for sustainability to become an important issue in China’s seafood markets. We find that clusters of perceptions about cultural status, quality, health and food safety, and country of origin influence decisions that consumers make. These norms are rooted in sociocultural practice and drive current trade strategies. While traders do want to mitigate risks and secure supplies, food safety, product quality and country of origin are viewed as more important concerns than stock sustainability. Responsibility for sustainable fishing is perceived to be that of national governments in production countries. Trading practices and consumer perceptions together pose a serious challenge to sustainable seafood markets, further confounded by clandestine cross-border grey trade into China.